MODELLING HUMAN PERIPHERAL TISSUE TEMPERATURE BASED ON NUMERICAL COMPUTATION OF NON-LINEAR BOUNDARY VALUE PROBLEM - Khanday, M. A.; Nazir, K.; Rasool, N. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2016)
A mathematical model has been established to analyse the changes in the tissue temperature on the peripheral regions of human body with respect to varying physiological conditions. The formulation is based on a parabolic heat equation with appropriate physiological parameters. The solution has been established using finite difference scheme and the simulation was done with the help of MATLAB software. It has been observed that the results have shown a considerable effect on temperature profiles due to variable physiological parameters.